أثر العبئ الضريبي على مردودية المؤسسة الإقتصادية دراسة حالة مؤسسة مطاحن الأغواط 2015/2012 - جعمات زين العابدين; جعمات عمر الفاروق; بن ثابت علال (جامعة عمار ثليجي الاغواط, 2022)
The study aims to identify both the tax burden and the ways in which it is measured, as well as to identify the profitability of the economic institution, and to determine the impact of the tax burden on both commercial productivity and the economic and financial of the institution. That's how we tried to show this effect through an application research on the Laghouat Mills Foundation. Studying and analysing its financial lists for the period (2012-2015), where the study found a relationship A package between the tax burden and the commercial, economic and financial returns of this institution, which through the study is due to the support, exemptions and tax incentives that characterize this institution.